KhepOnTheWeb open access to a mobile robot on the Internet. - Saucy, P.
For years research has focused on ways to allow remote access via standard communication networks to unique or expensive structures. With the growth of the Internet, one finds more and more devices connected to it. Despite the fact that one may spy on other people with hundreds of cameras, it is currently possible to interact only with a few robots, which often have restricted access. To use a camera over the web, the user usually just sits and watches or sometimes has the ability to choose different camera orientation/views. With a robot, you have strong interaction. For instance, with a mobile robot equipped with an arm you can move along the floor and grasp objects. Discovering the control interface, the user has to understand rapidly the goal of the site and what the possibilities of the robot are in order to achieve them. The article analyses one year of netsurfer behavior regarding the use of KhepOnTheWeb, which was realized to demonstrate some possibilities of remote control of a Khepera mobile robot. After one year of access, we performed an analysis of the log files in order to understand the behavior of the public facing such an installation. This analysis was rather difficult because of the large amount of data involved, and specific software was developed in order to extract and present the relevant information. The goal of the project is presented, the hardware and software components of our robot installation are described, and the analysis of the web server log files is discussed. We also introduce another concept of a remote-controlled robot on the web
Keywords: KhepOnTheWeb; Khepera mobile robot; Control interface; Log files; Netsurfer behavior; Open access; Remote access; Web server